The Avian Diet Database as a source of quantitative information on bird diets - Allen H. Hurlbert (Nature Portfolio, 2021)
Measurement(s) Diet Technology Type(s) digital curation Factor Type(s) species Sample Characteristic - Organism Aves Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.15088245